Penerapan Technology Acceptance Model (TAM) dalam Menganalisis Minat Mahasiswa Menggunakan Metode Pembayaran Quick Response Code Indonesian Standard (QRIS) pada Bank Syariah - Muhamad Zaini El Wahyu; Melda Nur Fitriyani (STEBI Global Mulia Cikarang, 2021)
This study aims to analyze and conduct tests on the application of the technology acceptance model (TAM) in analyzing students' interest in using the payment method (QRIS) of Islamic banks in Islamic banking students of STEBI Global Mulia Cikarang Class of 2019-2021. This research was conducted using quantitative methods with descriptive and verification approaches. The sample in this study was collected using the slovin formula with an error rate of 5% and the sampling technique used was a non-probability sampling technique using purposive sampling where the resulting sample was 93 samples from a total of 120 populations. The analysis technique used is multiple linear regression. The results of this study can be concluded that partially the benefits variable has a significant effect on students' interest in using the payment method (QRIS) in Islamic banks with a t value of 3.900> 1.986 t table (df = 90). And the security variable significantly influences students' interest in using the payment method (QRIS) at Islamic banks with a t-value of 5.693> 1.986. Furthermore, the simultaneous effect with the F test shows that the benefits and safety significantly affect students' interest in using the Quick Response Code Indonesian Standard (QRIS) payment method at Islamic banks with an F calculated value of 90.727> 3.10.